(untitled) (Comprehensive Journal of Science, 2026)
In cryptography and computer security, Man-in-the-Middle (MITM) attacks represent a serious threat to the confidentiality and integrity of web communications. These attacks occur when an adversary secretly intercepts and possibly alters the communication between two parties who believe they are interacting directly . MITM attacks can be classified as passive, where the attacker observes communication, or active, where the attacker manipulates transmitted data . Successful execution requires the attacker to impersonate both communicating entities. Modern cryptographic protocols such as Transport Layer Security (TLS) use endpoint authentication through digital certificates issued by trusted Certificate Authorities (CAs) to ensure secure communication . However, as attackers evolve, traditional defenses may no longer suffice. This research explores novel cryptographic algorithms and enhanced security mechanisms to strengthen web services against MITM attacks. The study focuses on improving authentication, secure key exchange, and data integrity verification techniques to create more resilient and trustworthy web service architectures.